Association between prophylactic low‐molecular‐weight heparin use in pregnancy and macrosomia: analysis of the Ottawa and Kingston birth cohort. (8th January 2019) - Lowry, D. E.; Corsi, D. J.; White, R. R.; Guo, M.; Lanes, A.; Smith, G.; Rodger, M.; Wen, S. W.; Walker, M.; Gaudet, L.
Abstract : Essentials Low‐molecular‐weight heparin (LMWH) is used to prevent venous thromboembolism (VTE) in pregnancy. We evaluated the association between LMWH and large for gestational age (LGA) infants. We found no significant associations between LMWH use and LGA. LMWH does not appear to increase the risk for the delivery of an LGA infant. Summary: Background: Low‐molecular‐weight heparin (LMWH), an anticoagulant, is the recommended drug for thromboprophylaxis and treatment of venous thromboembolism (VTE) in pregnancy. During pregnancy, LMWH is routinely prescribed to mothers with an increased risk of VTE or with a history of thrombosis. Although clinical reports of larger offspring born to women administered LMWH have been noted, no studies to date have evaluated or associated the use of LMWH and large for gestational age (LGA) infants. Objectives: To determine whether there is an association between LMWH usage in mothers and the prevalence of LGA. Patients/Methods: We performed an analysis of the Ottawa and Kingston (OaK) Birth Cohort and report characteristics of LMWH and association LGA (> 10%ile). We used coarsened exact matching (CEM) methods to account for bias and confounding. Results: A total of 7519 women from the OaK Birth Cohort were included; 59 were administered LMWH during pregnancy (0.78%). Mothers prescribed LMWH had significantly greater BMI ( P = 0.0001), age ( P = 0.0001) and parity ( P = 0.02). Gestational length was shorter among women administered LMWH compared to those without treatment (37.7 ± 2.0 vs. 39.2 ± 2.0, P < 0.0001), an iatrogenic finding. The odds ratio of an LGA delivery among women administered LMWH was 1.02 (95% confidence interval [CI], 0.48–2.16; P = 0.96) in unadjusted analyses and was 1.15 (95% CI, 0.49–2.71) in the matched sample adjusted for maternal age, BMI and gestational age. Conclusions: These results, although exploratory, provide indirect evidence of no increased risk of LGA infants among women prescribed LMWH.